Investigation of perfluoroalkyl substances in proglacial rivers and permafrost seep in a high Arctic watershed. Issue 1 (15th December 2021) - MacInnis, John; De Silva, Amila O.; Lehnherr, Igor; Muir, Derek C. G.; St. Pierre, Kyra A.; St. Louis, Vincent L.; Spencer, Christine
Abstract : We measured perfluoroalkyl substances (PFAS) in proglacial rivers and along a non-glacial freshwater continuum to investigate the role of snow and ice melting in their transport and fate within the Lake Hazen watershed (82° N). Abstract : We measured perfluoroalkyl substances (PFAS) in proglacial rivers and along a non-glacial freshwater continuum to investigate the role of snow and ice melting in their transport and fate within the Lake Hazen watershed (82° N). PFAS concentrations in glacial rivers were higher than those in surface waters of Lake Hazen, suggesting melting glacial ice increased PFAS concentrations in the lake. Stream water derived from subsurface soils along a non-glacial (permafrost thaw and snowmelt) freshwater continuum was a source of PFAS to Lake Hazen. Lower concentrations were found downstream of a meadow wetland relative to upstream locations along the continuum, suggesting PFAS partitioning into vegetation and soil as water flowed downstream towards Lake Hazen. Our estimations indicate that total PFAS inputs from glacial rivers and snowmelt were 1.6 kg (78%) and 0.44 kg (22%), respectively, into Lake Hazen, totalling 2.04 kg, and the output of PFAS from Lake Hazen was 0.64 kg. A positive net annual change of 1.4 kg indicates PFAS had notable residence times and/or net storage in Lake Hazen.